TERPAAN MEDIA DI INSTAGRAM TERHADAP BRAND IMAGE - Fajar Nursanti, Sri Prapti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Instagram is not just social media for sharing photos and videos with others. However, it is also used to develop more companies and brands. Instagram is the third most popular social media in Indonesia. Previous studies have shown that Instagram as a media has an influence on the formation and development of brand image. This situation prompted researchers to undertake research into how much influence Instagram content, consisting of advertising content and other marketing content, has on the brand image of the @scarlett_whitening account. The aim of this study is to prove the influence of Instagram content used as information about scarlett whitening brand on the level of scarlett whitening brand image by testing the theory of ad exposure. The study used quantitative methods and used a questionnaire. As a sample of the study consisting of a hundred participants, it was distributed to followers of @scarlett_whitening account, the official Instagram account of @scarlett_whitening. Purposive sampling and non-probability sampling methods were used. The study found that there was a 37.8% influence of Instagram's social media profile on the brand image on the Instagram account @scarlett_whitening. The dimension of media attention and the dimension of brand image strength are the two dimensions that produce the highest value.